Processing Semblances Induced through Inter-Postsynaptic Functional LINKs, Presumed Biological Parallels of K-Lines Proposed for Building Artificial Intelligence - Vadakkan, Kunjumon I. (Frontiers in Neuroengineering, 2011)
The internal sensation of memory, which is available only to the owner of an individual nervous system, is difficult to analyze for its basic elements of operation. We hypothesize that associative learning induces the formation of functional LINK between the postsynapses. During memory retrieval, the activation of either postsynapse re-activates the functional LINK evoking a semblance of sensory activity arriving at its opposite postsynapse, nature of which defines the basic unit of virtual internal sensation - namely, semblion. Neuronal networks that undergo continuous oscillatory activity at certain levels of their organization induce semblions enabling the system to continuously learn, self-organize, and demonstrate instantiation, features that can be utilized for developing artificial intelligence (AI). Suitability of the inter-postsynaptic functional LINKs to meet the expectations of Minsky’s K-lines, basic elements of a memory theory generated to develop AI and methods to replicate semblances outside the nervous system are explained.